Microglial P2X7 receptor in the hypothalamic paraventricular nuclei contributes to sympathoexcitatory responses in acute myocardial infarction rat. (5th February 2015) - Du, Dongshu; Jiang, Meiyan; Liu, Min; Wang, Jin; Xia, Chunmei; Guan, Ruijuan; Shen, Linlin; Ji, Yonghua; Zhu, Danian
Highlights: Microglial P2X7 R in the PVN can be activated by endogenous ATP in rats with AMI. Activated P2X7 R might sensitise oxytocinergic (OT) and vasopressin (AVP) neurons. Sensitised OT and AVP neurons enhanced the peripheric renal sympathetic nerve tone. Abstract: Several pieces of evidence indicate that the microglial P2X7 receptor (P2X7 R) regulate cardiovascular activities. We explored the possible roles of microglial P2X7 R in the PVN mediated sympathoexcitatory responses in acute myocardial infarction (AMI) rat. Sprague–Dawley rats underwent coronary artery ligation to induce AMI. The rats received intraperitoneal administration of the P2X7 R antagonist Brilliant Blue-G (BBG, 25 or 50 mg kg −1, once a day for 5 days) prior to myocardial ischemia. Other rats received bilateral microinjection of P2X7 R-siRNA (0.015 or 0.03 nmol 0.1 μl per side, once a day for 2 days) targeting P2X7 R mRNA into the PVN prior to myocardial ischemia. First, we examined the ATP levels and protein expression P2X7 R in the PVN in different ischemia time groups, and we found that the change of P2X7 R was positive correlated with the ATP levels in a time-dependent manner. The double-immunofluorescence evidence showed that P2X7 R was mainly co-localizated with the microglial marker Iba-1 in the PVN. Second, gene knockdown of P2X7 R with P2X7 -siRNA or inhibition of P2X7 R with BBG reduce the mRNA and protein expression of IL-1β and TNF-α in the PVN of AMI rat. Third, microinjected P2X7 -siRNA also suppressed the up-regulation of P2X7 R, oxytocin and vasopressin in the PVN of AMI rats. Fourth, P2X7 -siRNA and BBG also attenuated the renal sympathetic nerve activity (RSNA) in the AMI rats. Our results indicate that microglial P2X7 R activation in PVN mediating the production of proinflammatory cytokines that activate oxytocinergic and vasopressinergic neuron, which augmented the RSNA in the AMI rat.